2017
DOI: 10.1123/japa.2015-0295
|View full text |Cite
|
Sign up to set email alerts
|

Opinions Toward Physical Activity, Sedentary Behavior, and Interventions to Stimulate Active Living During Early Retirement: A Qualitative Study in Recently Retired Adults

Abstract: This study aimed to obtain qualitative information about physical activity (PA) and sedentary behaviors (SB)and their determinants, and about recently retired adults' needs regarding PA interventions. Four focus group interviews were organized. The most commonly reported PA types were walking, cycling, swimming and fitness. The most commonly reported SB were reading, TV viewing, and computer use. Car use was limited. Most adults agreed their habits had changed during retirement. The most striking PA determinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 23 publications
6
51
0
1
Order By: Relevance
“…Among the 132 studies included, older adults valued PA participations and programs that emphasized "interaction with peers such as preferred group-based activity", "professional instruction", and "physical limitations such as discomfort and concerns about falling". Similar themes about older adult's perspectives on currently existing PA programs/interventions were found in Van Dyck et al [15]. Furthermore, older adults who were interviewed suggested new PA (e.g., aquafitness or LVB in this study), not just regular activities like walking and cycling, should be selected as intervention activities.…”
Section: Health Needs Of the Local Communitysupporting
confidence: 76%
“…Among the 132 studies included, older adults valued PA participations and programs that emphasized "interaction with peers such as preferred group-based activity", "professional instruction", and "physical limitations such as discomfort and concerns about falling". Similar themes about older adult's perspectives on currently existing PA programs/interventions were found in Van Dyck et al [15]. Furthermore, older adults who were interviewed suggested new PA (e.g., aquafitness or LVB in this study), not just regular activities like walking and cycling, should be selected as intervention activities.…”
Section: Health Needs Of the Local Communitysupporting
confidence: 76%
“…These findings could have been further amplified by the neighbourhood safety concerns also identified by this group (Hoppmann et al, 2015;Prins and van Lenthe, 2015). The theme of transportation (n = 14) has been extensively reported to be both a barrier and facilitator to PA participation among older adults (Bouma et al, 2015;Haselwandter et al, 2015;Kosteli et al, 2016;Van Dyck et al, 2017). Within the current study transportation was identified as a barrier (n = 10) restricting access to PA sessions regardless of living status.…”
Section: Enabling Correlatesmentioning
confidence: 65%
“…Many of the influencing factors that were identified in this study have been reported previously as being especially relevant to older people. In particular, poor health (Baert et al ., 2011; Bauman et al ., 2012), low motivation (Beck et al ., 2010; Moschny et al ., 2011), accessibility and cost issues (Mathews et al ., 2010; Van Dyck et al ., 2017) and a history of inactivity (Cousins and Keating, 1995; Friedman et al ., 2008; Telama, 2009; Buman et al ., 2010; Hirvensalo and Lintunen, 2011) have been frequently reported to be fundamental barriers to physical activity participation among older people in general. To a lesser degree, overestimation of current activity levels (Booth et al ., 2002), caring duties (Wilcox et al ., 2000; Buman et al ., 2010; Dickinson et al .…”
Section: Discussionmentioning
confidence: 99%